Analisis Kebutuhan Media Pembelajaran Interaktif pada Materi Asmaul Husna di Kelas V Sekolah Dasar - Radika Lesmana; Arini Anindya; Elfa Rahmawati; Nisa Fujianti; Anggi Maulana Rizqi (Lembaga Publikasi Ilmiah Universitas Islam Bunga Bangsa Cirebon, 2024)
This study aims to analyze the need for interactive learning media in Asmaul Husna material in class V in Islamic Religious Education (PAI) learning. This study used descriptive qualitative research method. The subjects in this study were one PAI teacher and 31 grade V students at SDN 1 Nagarawangi. The analysis in this study used the analysis of the Miles and Huberman model. The results of this study show that interactive learning media is needed in Asmaul Husna material in class V. So that this study can be concluded that interactive learning media is needed for teachers and students in learning in order to increase the enthusiasm and enthusiasm of learning students. Researchers recommend that further researchers be able to develop interactive learning media based on the needs analysis that has been done.Keyword : Needs Analysis; Interactive Learning Media; Asmaul Husna Material